Paul : the apostle of the Gentiles : journeys in Greece - Mavromataki, Maria (Athens, Greece : Haitalis, 2003)
Contents : v. VII : ke - *lys Includes bibliographical references.
Keywords: Paul -- the apostle, Saint -- missionary journeys; Bible. -- criticism, interpretation, etc